Cascade synthesis of uridine-5′-diphosphate glucuronic acid by coupling multiple whole cells expressing hyperthermophilic enzymes - Dan-Hua Meng; Ran-Ran Du; Lu-Zhou Chen; Meng-Ting Li; Fei Liu; Jin Hou; Yi-Kang Shi; Feng-Shan Wang; Ju-Zheng Sheng (Microbial Cell Factories, 2019)
Abstract Background Enzymatic glycan synthesis has leapt forward in recent years and a number of glucuronosyltransferase (EC 2.4.1.17) have been identified and prepared, which provides a guide to an efficient approach to prepare glycans containing glucuronic acid (GlcA) residues. The uridine 5′-diphosphate (UDP) activated form, UDP-GlcA, is the monosaccharide donor for these glucuronidation reactions. Results To produce UDP-GlcA in a cost-effective way, an efficient three-step cascade route was developed using whole cells expressing hyperthermophilic enzymes to afford UDP-GlcA from starch. By coupling a coenzyme regeneration system with an appropriate expression level with UDP-glucose 6-dehydrogenase in a single strain, the cells were able to meet NAD+ requirements. Without addition of exogenous NAD+, the reaction produced 1.3 g L−1 UDP-GlcA, representing 100% and 46% conversion of UDP-Glc and UTP respectively. Finally, an anion exchange chromatography purification method was developed. UDP-GlcA was successfully obtained from the cascade system. The yield of UDP-GlcA during purification was about 92.0%. Conclusions This work built a de novo hyperthermophilic biosynthetic cascade into E. coli host cells, with the cells able to meet NAD+ cofactor requirements and act as microbial factories for UDP-GlcA synthesis, which opens a door to large-scale production of cheaper UDP-GlcA.